2010
DOI: 10.1577/t09-180.1
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance, Growth, and Mortality of Five Age‐0 Estuarine Fishes in Relation to Discharge of the Suwannee River, Florida

Abstract: Understanding the relationships between river discharge and recruitment of estuarine fishes is important because of hydrological alterations caused by anthropogenic water withdrawals. Varying river discharge alters salinity, turbidity, nutrient levels, and detrital concentrations, all of which affect estuarine biota. The lower Suwannee River, Florida, is one of the few remaining large-river systems in the United States that has no major impoundments. We assessed the relationship between seasonal river discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…As noted by Estevez (2002), single-species analyses have tended to be more common than community-or assemblage-level assessments in estuarine inflow studies; the present study integrated both methods. Changes in habitat extent of the oligohaline zone and associated biota form an important component in the determination of appropriate freshwater inflows to estuaries, along with other factors such as secondary production (e.g., abundance and growth of fish; Purtlebaugh and Allen 2010). In studies that aim to track fish distributions in relation to changing isohalines, we recommend sampling much farther upriver than mean conditions indicate would be necessary, to capture the effects of events such as drought or the long-term effects of water withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by Estevez (2002), single-species analyses have tended to be more common than community-or assemblage-level assessments in estuarine inflow studies; the present study integrated both methods. Changes in habitat extent of the oligohaline zone and associated biota form an important component in the determination of appropriate freshwater inflows to estuaries, along with other factors such as secondary production (e.g., abundance and growth of fish; Purtlebaugh and Allen 2010). In studies that aim to track fish distributions in relation to changing isohalines, we recommend sampling much farther upriver than mean conditions indicate would be necessary, to capture the effects of events such as drought or the long-term effects of water withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Attributing population dynamics to particular causal mechanisms is, however, difficult because biomass or abundance indices are an integration of demographic and behavioural processes that operate at different temporal and spatial scales (Robins et al, 2005). Repeated observations of recruitment (Staunton-Smith et al, 2004;Jenkins et al, 2010), growth (Robins et al, 2006;Purtlebaugh & Allen, 2010;Stocks et al, 2011;Glover et al, 2013) and behaviour (Crook et al, 2010;Walsh et al, 2013) provide the finer resolution needed to understand population dynamics and individual responses to environmental variability in estuaries. Better still, concomitant measures of these processes facilitate a more complete, in-depth understanding of a species' response to environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Increased freshwater input can affect the recruitment, residence time, and location of fishes in an estuary, as well as altering fish assemblages and abundance, especially of marine forage fishes (Jassby et al 1995;Loneragan and Bunn 1999;Purtlebaugh and Allen 2010). Weitkamp et al (2012) found reduced fish abundance and altered species representation in 2008, 2010, and 2011, years of unusually high discharge for the Columbia River, and reported that these Bnatural experiments for the influence of flow^resulted in both a decrease in numbers of marine forage fishes, especially northern anchovy and Pacific herring, and a decrease in residence time for juvenile salmonids.…”
Section: Discussionmentioning
confidence: 99%